Fungal Infections among Teledermatology Consultations in Dermatology Department of a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Sagar Mani Jha (Nepal Medical Association, 2021)
Introduction: Teledermatology provides virtual consultation to patients using telecommunication technology. Using this method dermatologists can diagnose a condition with the help of pictures of the lesions and short history. During the COVID-19 pandemic, practicing this method has become more relevant. Providing teleconsultations to patients with fungal skin infections can prevent inadvertent use of topical corticosteroids. The objective of this study was to find the prevalence of fungal infections among teledermatology consultations done in a tertiary care hospital.